Measure the ratios of fatty acids to some Gram negative bacteria - Ameera Al-Rawi; Ghada Altaee; Shafaq Burhan (College of Education for Pure Sciences, 2007)
Fatty acids were analyzed from cell wall and cell membrane of some gram negative bacteria Pseudomonas aeruginosa, Plesimonas shigelloides and Proteus mirabilis by using gas liquid chromatography (GLC). Extraction and methylestrification analysis were done and compared with standard fatty acids. The results showed that the major percent of fatty acids was lionleic acid (14.137o/o) in Ps. aeruginosa followed by palmitic acid (10.059%) the other fatty acids percent myrestic acid, stearic acid, oleic acid, capric acid, lauric acid were different and it was 0.527%, 8.042%, 6.261%, 1.205%, 0.527% respectively. While the higher percent of fatty acids in Plesimonas shigelloides was palmitic acid (20.621 %) followed by oleic acid (15.816%), stearic acid (15.373%) and myrestic acid (10.897%). The minor percent which was less than 1% belonged to lauric acid, capric acid, docosahexanoic acid, eicosapentanoic. For Proteus mirabilis, myristic acid and lauric acid appeared with higher percent 17.349%and 13.130% respectively.